2019
DOI: 10.20944/preprints201908.0117.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Astragalus Polysaccharides (PG2) Enhances the M1 Polarization of Macrophages, Functional Maturation of Dendritic Cells, and T Cell-Mediated Anticancer Immune Responses in Patients with Lung Cancer

Abstract: Background: Recently we demonstrated that Astragalus polysaccharide (PG2), the active ingredient in dried roots of astragalus membranaceus, ameliorates cancer symptom clusters and improve quality of life (QoL) in patients with metastatic disease by modulating inflammatory cascade, against the background that inflammatory cells including macrophages, dendritic cells (DCs), and cytotoxic T lymphocytes (CTLs) in tumor initiation, metastasis, and progression. Nevertheless, the role of PG2 in the modulation of anti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The proportions of M1 and M2 macrophages in TAMs were examined by flow cytometry as previously reported (Bamodu et al. 2019 ). In brief, TAMs suspension (100 μL) was incubated with 10 μL anti-human CD80-FITC (Thermo Fisher Scientific, Waltham, MA, USA) or anti-human CD206-APC (Thermo Fisher Scientific) antibodies at 4 °C for 1 h in the darkness.…”
Section: Methodsmentioning
confidence: 99%
“…The proportions of M1 and M2 macrophages in TAMs were examined by flow cytometry as previously reported (Bamodu et al. 2019 ). In brief, TAMs suspension (100 μL) was incubated with 10 μL anti-human CD80-FITC (Thermo Fisher Scientific, Waltham, MA, USA) or anti-human CD206-APC (Thermo Fisher Scientific) antibodies at 4 °C for 1 h in the darkness.…”
Section: Methodsmentioning
confidence: 99%
“…A study showed that treatment with APS suppressed the replication of avian infectious bronchitis coronavirus in chicken embryo kidney (CEK) cells by reducing the expression of inflammatory cytokines (IL-1, IL-6, IL-8, TNF-α) [207]. Further, it has been reported that APS promoted immunity and exerted anti-tumorigenic property by modulating TLR4 mediated MyD88 dependent signalling pathway [210,211]. Recently, a study revealed that it ameliorated the Salmonella typhimurium induced inflammation in diarrhea mice model by balancing the GUT flora of mice that maintains the intestinal integrity by enhancing the tight junction proteins viz.…”
Section: Anti-inflammatory and Health Mediated Properties Of Astragalus Membranaceusmentioning
confidence: 99%
“…Adding PG2 to cisplatin, a conventional chemotherapeutic drug, can synergistically increase the antitumor effect (105). According to the above theory, the effective results of immunotherapy combined with PG2 in NSCLC were expected (106). Phytolacca acinosa polysaccharides I (PAP-1) is a compound of Phytolacca, which has been proven to affect immune functions in mice.…”
Section: Icis Combined With Traditional Chinese Medicine (Tcm)mentioning
confidence: 99%